Analisis Kebijakan Pendidikan Terkait Strategi Peningkatan Kinerja Guru Beserta Faktor yang Mempengaruhinya - Rizki Ananda; Rahmi Gusliana; Salma Juita HR; Khairiyatun Nisa’ (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
Teacher performance continues to be in the spotlight in the world of education. Expectations for good teacher performance are what the community wants. With good teacher performance, it is hoped that it will produce quality students. This study aims to determine strategies for improving teacher ferformance and the factors that influence it. The study used the study literature method. In this study the results showed that the factors that influence teacher performance are the leadership of the principal, work facilities, evalution and supervision. While the strategy for improving teacher performance is carried out through the application of KASAH : 1) increasing knowledge, 2) increasing ability, 3) increasing skills, 4) increasing self attitude 5) developing habits.